Bibliometric Analysis of Trends in Risk Factors in Melasma - Yuli Wahyu Rahmawati; Ali Mustofa (Universitas Muhamadiyah Manado, 2026)
Risk factors for melasma have been identified at several points such as the use of birth control pills, cosmetics, sun exposure, estrogen therapy, decreased thyroid and ovarian function, ovarian tumors, nutrition, drugs that are classified as phototoxic or photoallergic, and epilepsy drugs. This article aims to determine the incidence of melasma and its risk factors. This study uses articles collected from the Google Scholar database. The data collection step uses the keyword